PEMBANGUNAN HUTAN KOTA DI KOTA CIREBON - Novianti Muspiroh (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2014)
Cirebon is a growing city that is characterized by fast population growth. It influences on increase of needs, residential land, recreation, transportation, health, education, and other facilities that support the sustainability of social and economic life of Cirebon city dwellers. The development of industrial areas and the use of means of transportation, such as motorcycles and cars can cause pollution or contamination. Meanwhile, Cirebon is a coastal city which has a hot temperature. Therefore, Cirebon requires urban open space as a solution to the problem in order to create beautiful, cool, pollution free of the city lungs and the availability of public space to relieve fatigue from urban tension. Unfortunately, the local government provids only 9% city forest from 30% the ideal of the total area.Not to mention that the existing urban open space, actually, seem to be ignored. This situation is certainly not healthy for the life quality of Cirebon city dwellers.Key words: Hutan, Kota, Pembangunan, Manfaat